2011
DOI: 10.1186/1477-7517-8-5
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of AIDS and HIV transmission among drug users in Rio de Janeiro, Brazil

Abstract: BackgroundProper knowledge of HIV transmission is not enough for people to adopt protective behaviors, but deficits in this information may increase HIV/AIDS vulnerability.ObjectiveTo assess drug users' knowledge of HIV/AIDS and the possible association between knowledge and HIV testing.MethodsA Cross-sectional study conducted in 2006/7 with a convenience sample of 295 illicit drug users in Rio de Janeiro, assessing knowledge on AIDS/HIV transmission and its relationship with HIV testing. Information from 108 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
(35 reference statements)
1
12
2
2
Order By: Relevance
“…This finding is fairly similar to the findings of studies in Rio de South East Asia Journal of Public Health 2017;7(1):42-47 Table 3: Association between respondents' level of knowledge and socio-demographic variables (n=200) was found to be higher in a study among drug-users in Brazil. 23 One possible reason for the difference between the findings of the two studies could be that the Brazilian study was conducted among all types of drugusers whereas our study included only IDUs. Another possible explanation is the lower educational level of our interviewees.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…This finding is fairly similar to the findings of studies in Rio de South East Asia Journal of Public Health 2017;7(1):42-47 Table 3: Association between respondents' level of knowledge and socio-demographic variables (n=200) was found to be higher in a study among drug-users in Brazil. 23 One possible reason for the difference between the findings of the two studies could be that the Brazilian study was conducted among all types of drugusers whereas our study included only IDUs. Another possible explanation is the lower educational level of our interviewees.…”
Section: Discussionmentioning
confidence: 40%
“…22 It may be due to the fact that the education system in those countries has been affected by two Janeiro, Brazil, and Kabul, Afghanistan. 23,24 It appears that a major gap in knowledge exists among drug-users about the means of transmitting/ acquiring HIV. Correct response about treatment of HIV/AIDS (68%) was considerably higher among our study participants compared to the findings of the study in Vietnam on most-at-risk populations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they showed accurate knowledge about HIV transmission and prevention, but for a significant part of the sample sharing injecting materials still happens. These results did not corroborate the notion that the lack of accurate information about HIV transmission and prevention increases the vulnerability to the infection (Goncalez et al, 2010) or less HIV serostatus testing (Bertoni et al, 2011). In fact, almost all the participants in the current study were tested for HIV, and 85% of them know that "they can be infected with HIV by sharing syringes with someone with HIV", but about a third shared syringes or other materials, and half of them shares materials in general.…”
Section: Discussioncontrasting
confidence: 44%
“…Their study concluded that, high risk of HIV transmission existed among drug users compared to general population. Study also proposed that incorrect knowledge about HIV/ AIDS may be a barrier for HIV testing in-time and interventions should be planned to such category of people [16,17].…”
Section: Review Of Literaturementioning
confidence: 99%